2002
DOI: 10.1016/s0029-7844(01)01683-0
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intraepithelial neoplasia III: long-term follow-up after cold-knife conization with involved margins

Abstract: Expectant management is reasonable for patients with CIN III and positive margins after cold-knife conization. However, these patients require careful follow-up, particularly during the first year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 14 publications
6
64
1
9
Order By: Relevance
“…Removing CIN does not necessarily eliminate persistence of the HPV infection as shown by the frequency of recurrence of CIN after LEEP [39]. Administration of immunotherapies such as HspE7 may be an attractive alternative to ablative surgical intervention for a subset of women with high-grade CIN yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…Removing CIN does not necessarily eliminate persistence of the HPV infection as shown by the frequency of recurrence of CIN after LEEP [39]. Administration of immunotherapies such as HspE7 may be an attractive alternative to ablative surgical intervention for a subset of women with high-grade CIN yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30%-50% of patients with positive margins were found to have no residual tumor on subsequent hysterectomy. In addition, several studies report on the feasibility of conservative management for patients with CIN 3 who had positive resection margins after conization but did not develop persistent or recurrent disease [8,17,18]. This suggests that conservative management of patients with stage IA1 cervical cancer might be feasible even if the resection margin evidenced a high-grade lesion without invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…As such, further treatment for residual neoplasia can be seen to depend on the margin status of the conization specimen [6,8]. Recent reports have suggested that patients with stage IA1 squamous cell carcinoma can be managed conservatively after conization and vaporization, even when the conization specimen had positive margins but no invasive disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the relatively high rate of clearance (95% (Reich et al, 2002)), patients after conisation due to CIN2 -3 are at a higher risk of developing residual or recurrent disease than controls. Their regular follow-up protocol after conisation includes continued cytological and colposcopic examination as well as reconisation in cases of suspected residual/recurrent lesions (Milojkovic, 2002).…”
Section: Discussionmentioning
confidence: 99%